Rancang Bangun Expert System Diagnosa Penyakit Mata Manusia Menggunakan Metode Certainty Factor - Anna, Anna; Annisa, Riski; Rahayuningsih, Panny Agustia; Nurdiani, Siti (Infotek: Jurnal Informatika dan Teknologi, 2024)
When the eyes experience interference, the sufferer will be very uncomfortable in doing their daily activities. In an expert system, the Certainty Factor methods are used to determine the percentage of possible eye diseases suffered and provide accurate diagnostic information based on research conducted. The expert system developed to diagnose eye disease has been successfully implemented using knowledge which includes 22 symptoms and 6 types of related diseases. The purpose of this study is to explore the symptoms displayed in the form of questions in order to diagnose the type of disease with web management system-based software. So that later it gives the results of the percentage of diagnosis of eye disease after based on the symptoms suffered. Of course this research can help experts in dealing with existing problems and make it easier for the general public to get information about eye diseases directly consult through the system without having to check with an eye doctor first, can also provide relief for the underprivileged people who want to consult directly with experts only through Web application.